Computational and experimental characterization of drug release kinetics in trabecular bone from titania nanotube implants - Kaiser, J; Buenzi, PR; Moom, Sin Aw; Khalid, Kamarul Ariffin; Gulati, Karan; Atkins, Gerald J; Pivonka, Peter; Findlay, David M; Losic, Dusan (2012)
Local drug delivery using drug-releasing implants located inside bone is recognised as a promising strategy to address the limitations of systemic drug administration to bone. However, the studies of drug-release kinetics are not possible to perform using existing in-vitro drug releasing systems and 2-D bone cell models. The aim of this work is to demonstrate the use of a 3-D bone bioreactor for studying the drug-release kinetics and distribution of drugs in the ex-vivo cancellous bone environment. Bovine trabecular bone was used as the bone substrate, in which drug-releasing implants were embedded in the form of nano-engineered titanium wires covered with a layer of titania nanotube (TNT) arrays. A hydrophilic fluorescent dye (rhodamine B) was used as a model drug, loaded inside the TNT/Ti implants to monitor drug release and transport in trabecular bone under ex-vivo conditions. In order to better understand how the bioreactor perfusion rate and the local drug release from the titanium wire affect overall drug distribution in the bone sample we utilize 3D finite element modelling. This model is based on porous media theory and takes into account advective-diffusive transport of the drug through the micropores of bone. The results showed a consistent, gradual release of model drug from the TNT/Ti implants, with a characteristic three-dimensional distribution into the surrounding bone over a period of 5 days. These results demonstrate the utility of this system for ex-vivo drug release studies in bone, which can be applied to optimise the administration therapeutics in bone for specific therapies and design of new drug delivery systems.